Quelques aspects botaniques et nutritionnels des pâturages du dromadaire en Algérie - Longuo F.H.; Chelma A.; Ouled Belkher A. (Séminaire sur la digestion, la nutrition et l'alimentation du dromadaire, 1989)
An investigation was conducted in the areas of Ouargla, Ghardaïa and El-Goléa in view of on the one hand, inventorying plants picked by the dromedary, and on the other hand, studying their chemical composition and their digestibility. 6 plants were thus examined: 3 'Acheb' and three perennial plants. It appears that: the ash composition is significantly higher for the 'Acheb' than for the perennial plants. As concerns total nitrate matters, the content varies from 6 to 12 per cent, and 4 to 9 per cent respectively for the 'Acheb' and the perennial plants. On the other hand perennial plants are richer in parietal compounds evaluated in NDF. As concerns in vitro digestibility of dry matter, the best results are obtained with the 'Acheb'.
Séminaire sur la Digestion, la Nutrition et l'Alimentation du Dromadaire, 1988/02/27-1988/03/01, Ouargla (Algeria)